Architectural design, church beliefs, visual imagery and project finance as predictors of church satisfaction in the Five Boroughs of New York - Basurto Gutiérrez, Karla Saraí; Louisy Daisley, Bernard Ellsworth (Anuario de Investigación UM, 2020)
The empirical model in which architectural design, church beliefs, visual imagery and project finance are predictors of satisfaction, as perceived by the clergy and members of Seventh-day Adventist churches in the five boroughs of New York City, New York, USA.